The preschool ‘moment’ - tracking the relationships between early childhood development, socioeconomic status and Demographic Indicators among pre-schoolers in Soweto. - Jugdav, Sasha (My University, 2019)
Insight into early childhood development across various socio-economic contexts has yielded valuable and informative results on the relationship between development and environment. Though previous studies have contributed immensely to supporting the positive relationship between socio-economic status and development, studies coming from low-income and non-Western contexts are challenging this well-established relationship. This is the cornerstone on which the presented study is based. Objective: The primary aim of this study was to investigate the relationship between socioeconomic status, demographic indicators and early childhood development (ECD) components amongst preschool children from Soweto, a low-income setting in South Africa. The secondary aim was to compare the performance of South African preschool children with performance of preschool children from Australia and America on the same ECD measures. Methods: Thirty-six preschool children aged three to five years old were assessed on three measures of ECD encompassing cognitive, motor and socio-emotional skills. These measures were the Early Years Toolbox for executive function (cognitive skills), Ages and Stages Questionnaire 3rd edition for fine and gross motor skills and the Pediatric Evaluation of Emotions, Relationships and Socialisation for emotion recognition and emotion perception (socio-emotional skills). Socioeconomic status was considered in terms of access to services, amenities (e.g. flushing toilets and running water) and resources (e.g. computers, televisions, cell phones). Demographic variables included age and sex. Relationships between these variables were analysed by means of correlations and linear regressions. Comparisons between study and norm data were established by means of independent samples t-tests and descriptive statistics. Results: Contrary to the majority of literature, preschool children from Soweto performed better than normative scores from an Australian sample on two executive function tasks and on fine motor skills compared to American norms. The Sowetan sample, however, performed worse than their normative counterparts on socio-emotional skills. Better socioeconomic status was found to be related to fewer errors on emotion perception, however it was also related to worse performance on visuo-spatial memory. There were no significant sex differences on task performance and minimal differences in performance between older and younger children. Conclusion: These findings show that the relationship between socioeconomic status and ECD may differ across different contexts which merits further investigation. Results also indicate that the Sowetan sample show better than expected performance on impulse control, visuo-spatial working memory and fine motor skills considering the economically challenged contexts from which they come. Future research investigating these trends in similar contexts is encouraged.
A research report submitted in partial fulfilment for the degree Master of Arts in Social and Psychological Research by Coursework and Research Report (PSYC7022) in the Department of Psychology, Faculty of Humanities, School of Human and Community Development at the University of the Witwatersrand Johannesburg, 2019